Perception of Availability and Accessibility of Computer Based Test Facilities Among Upper Basic Science Students in Sabon Gari and Zaria, Nigeria - Jesulowo, J. F.; Udeh, S. E.; Abubakar, S.; Abdulkadir, K.; Adamu, A. Y.; Yahaya, I. A. (Kashere Journal of Education, 2025)
This study investigated the perception of availability and accessibility of Computer-Based Test facilities (CBT) among upper basic science students in the Sabon Gari and Zara Local Government Areas of Kaduna State, Nigeria. Two research questions and two null hypotheses guided the conduct of the study. The methodology employed a descriptive survey research design. A sample of 380 students was selected from a population of 33,425. Questionnaire titled perception of availability and accessibility were validated with a reliability coefficient of 0.7 used for data collection. We used the Chi-square test to identify any significant differences in the students' perceptions of the availability and accessibility of computer facilities. The Mann-Whitney U test was used to compare the mean scores of the two Local Government Areas on the perception of CBT effectiveness. Results indicate significant differences between the two Local Government Areas in facility availability and accessibility and their perceptions of effectiveness were similar. The findings point out that it requires equitable resource distribution and improved ICT access to enhance CBT implementation among basic schools’ students. A recommendation, among others, is to improve ICT infrastructure and access in schools, especially in underserved areas.